Recent Development of Max-SNR Opportunistic Scheduling in Cross Layer Design - Praveena, T. (Research Highlights in Mathematics and Computer Science Vol. 7, 2023)
Wireless spectrum efficiency is crucial to meet the growing demand for wireless services, particularly low-cost cellular Internet services. In contrast to wired networks, wireless channels feature location and time-varying. At any one time, various channel conditions affect various wireless users. A cross-layer design technique called opportunistic scheduling is used to take advantage of the wireless environment's time-varying characteristics and boost system performance overall while still meeting user-specified Quality of Service (QoS) and fairness standards. Opportunistic algorithms' fundamental premise is to schedule a user with the optimum channel condition at a specific moment by taking advantage of channel changes. The demand for QoS provisioning cannot be met by a plan that only permits users with the best channel conditions to transmit at high transmission powers. Using the Max-Min fair algorithm, the project's goal is to create opportunistic scheduling while upholding fairness and QoS requirements. The Media Access Control (MAC) layer has been equipped with an opportunistic scheduler that employs Max-Min fairness scheduling. Here, the base station collects the Signal to Noise Ratio (SNR) of all the nodes and then schedules the users based on these SNR values using the Max-Min algorithm. Strict Priority, a non-opportunistic scheduling technique, is then used to accomplish the identical scenario. The throughput, fairness, delay, and jitter of the two resulting algorithms are then contrasted.